Diversity, composition and distribution of bracket fungi in Mt. Arayat Protected Landscape, Pampanga, Philippines - REYNANTE G. BUSTILLOS; JOHN MARCO T. DE GUZMAN; EMERITA S. CAYMO (Society for Indonesian Biodiversity, 2025)
Abstract. Bustillos RG, De Guzman JMT, Caymo ES. 2025. Diversity, composition and distribution of bracket fungi in Mt. Arayat Protected Landscape, Pampanga, Philippines. Biodiversitas 26: 4954-4966. Despite its recognition as a protected area, little attention was given to the macrofungal diversity of Mt. Arayat Protected Landscape (MAPL), Pampanga, Philippines. This study investigated current diversity of wood-inhabiting fungi in three collection sites of MAPL (i.e., North Peak, South Peak, Pinnacle) and varying elevation gradients (i.e.,100-250, 251-500, 501-750 masl). Bracket fungi were purposively collected and characterized using morphological properties and further validated by experts. A total of 47 species were identified, belonging to the class Agaricomycetes and grouped into 4 orders, 7 families, and 14 genera. Out of these, 32 species were identified down to the species level, while 15 were at the genus level and require DNA barcoding to confirm their identities. The order Polyporales and genus Ganoderma recorded the highest number of species. The majority of the bracket fungi were anchored on dead logs, living solitary and are non-edible. Shannon and Simpson diversity indices showed that the South Peak has the highest fungal diversity and richness. The three collection areas have almost even distribution of species. Sorensen index reveals high similarity of species found among collection sites. Moreover, diversity according to altitude is highest at 251-500 masl with moderate richness and even distribution of species. Only 251-500 masl and 501-750 masl share similar species, while slight variations are observed in other elevation ranges. This pioneering report on diversity of MAPL reflects its forest status that can be used as baseline information for continuous monitoring of its condition and contribute to biodiversity conservation and sustainability efforts.